Man and woman : an inside story - Pfaff, Donald W., 1939- (New York : Oxford University Press, 2011)
"The saga of sex differences in brain and behavior begins with a tiny sperm swimming toward a huge egg, to contribute its tiny Y chromosome plus its copies of the other chromosomes. Genetic, anatomic and physiologic alterations in the male ensue, making his brain and behavior different in specific respects from his sister. Brain-wise, specific cell groups develop differently in males compared to females, in some cases right after birth and in other cases at puberty. But genetics and neuroanatomy do not dominate the scene. Prenatal stress, postnatal stress and lousy treatment at puberty all can affect males and females in different ways. The upshot of all these genetic and environmental factors produces small sex differences in certain abilities and huge sex differences in feelings, in pain and in suffering. Put this all together and the reader will see that biological and cultural influences on gender roles operate at so many different levels to influence behavioral mechanisms that gender role choices are flexible, reversible and non-dichotomous, especially in modern societies."--Book jacket.
What scientists fight about when they fight about sex -- Chromosomes for him and her -- Hormones on the brain -- Neonatal hormones, brain structure, and brain chemistry -- Mating and parenting -- Males fighting -- Females befriending (males, too) -- Pain and suffering -- Perilous times : newborns and adolescents -- Sex gone wrong -- Bottom line.
Includes bibliographical references and index.
Keywords: Sex differences (Psychology); Sex differences; Sexual Behavior -- psychology; Brain Chemistry; Gender Identity; Hormones; Sex Characteristics